Unpacking Academic Predictors of English Proficiency in Indonesian Higher Education - Skolastika, I Made Perdana; Wijaya, I Putu Agus Wijaya Kusuma; Widiantara, Dewa Sang Made Widiantara (Journal of Educational Study, 2025)
This study aims to investigate whether students’ cumulative Grade Point Average can serve as a predictor of their English proficiency as measured by an institutional English test. The research addresses the broader question of how general academic achievement relates to language competence in higher education settings. Employing a quantitative correlational design, data were collected from 115 undergraduate students who had both an officially recorded Grade Point Average and an institutional English proficiency score. Pearson’s product–moment correlation and simple linear regression analyses were used to examine the relationship and predictive strength between the two variables. The findings reveal a moderate and positive correlation (r = 0.55, p < 0.001), indicating that students with higher academic performance tend to achieve better results on the English proficiency test. The regression model was significant, explaining 30.3 percent of the variance in English scores (F= 49.03, p < 0.001). The resulting equation confirms that general academic achievement is a meaningful predictor of language performance. These results highlight the potential use of Grade Point Average as one indicator of readiness for English proficiency benchmarks in higher education. The study also suggests that other factors, such as language exposure, motivation, and learning strategies, may contribute to unexplained variance and should be explored in future research.